Both temporal and spatial aspects of predator management influence survival of a temperate ungulate through early life - McMillan, Brock R.; Hall, Jacob T.; Freeman, Eric D.; Hersey, Kent R.; Larsen, Randy T. (Frontiers in Ecology and Evolution, 2023)
Recent meta-analyses indicate that predator removal experiments result in marginal increases in prey abundance at best. However, most predator removal studies take place for less than the target prey’s generation time and lack a targeted spatial approach. Our objective was to determine how temporal and spatial aspects of predator control influenced neonate survival of a temperate ungulate. We conducted multiyear coyote (Canis latrans) removals using a crossover experimental design. We found that consecutive years of predator removal increased survival of neonate mule deer (Odocoileus hemionus) more than a single year of removal. We also found that removing coyotes from areas near fawn birth sites increased fawn survival, whereas removing coyotes from areas farther from birth sites did not influence fawn survival. Our results underscore the need for coyote removal programs to (1) employ removal efforts over consecutive years to maximize effectiveness, (2) conduct spatially explicit removal efforts targeting fawning habitat, and (3) occur when the likelihood of additive mortality is high and prey populations have the resources available to grow.